Table_1_Diversity of Cultivable Microbes From Soil of the Fildes Peninsula, Antarctica, and Their Potential Application.DOCX - Bailin Cong; Xiaofei Yin; Aifang Deng; Jihong Shen; Yongqi Tian; Shaoyun Wang; Huanghao Yang (2020)
To explore the diversity and application potential of Antarctic microorganisms, 1208 strains bacteria and fungi were isolated from 5 samples collected from the Fildes Peninsula during China’s 27th and 31st Antarctic expeditions. By using 16S and ITS sequence similarity alignment, 83 strains bacteria belonging to 20 genera and 30 strains fungi belonging to 7 genera were identified. Among them, 1 strains bacteria and 6 strains fungi showed low sequence similarity to the database, suggesting that they might be novel species. Physiological-biochemical characteristics showed that the identified bacteria could utilize many kinds of carbohydrates and that the identified fungi could produce several kinds of extracellular enzymes. The fungal strain MS-19, identified as Aspergillus sydowii, possesses the potential to produce antifungal activity agents based on an activity-guided approach. Further isolation yielded four polyketones: versicone A (1), versicone B (2), 4-methyl-5,6-dihydro-2H-pyran-2-one (3), and (R)-(+)-sydowic acid (4). It should be noted that 1 displayed strong activity against Candida albicans, with an MIC value of 3.91 μg/mL.